Implementasi Metode Local Binary Pattern (LBP) Dan K-Nearest Neighbor (K-Nn) Pada Sistem Berpakaian Di Prodi Teknik Informatika Universitas Pelita Bangsa - Isarianto; Helmi Ahmad Fauzi Candra (Prosiding Sains dan Teknologi, 2024)
The student code of ethics is a set of rules that regulate students' attitudes, words, actions, appearance, and clothing while they are students. Pelita Bangsa University students also follow the development of fashion trends from fashion developments every year, which will have an impact on the dress code of ethics for students of the Pelita Bangsa University Faculty of Engineering. Dressing neatly and politely means wearing formal clothes when participating in campus activities. Several lecturers require wearing formal (collared) clothing when participating in learning activities. Research has been proposed to detect clothing using the Local Binary Pattern (LBP) method with the K-Nearest Neighbor (KNN) classification. 130 images were used with a composition of 70 images of t-shirts and 60 images of shirts. This system is used to detect t-shirts and shirts. A system will be designed to detect shirts that focus on Pelita Bangsa University students using the Local Binary Pattern (LBP) and K-Nearest Neighbor (KNN) methods as classifiers. It is hoped that the results of testing this research can get better accuracy than previous research. This accuracy was obtained from testing 130 images using the Lbp extraction method with values of R=1 and P=8, in addition to the KNN classification with values of K=1 and Euclidean distance parameters.